The Effect of Different Drying Methods on Bioactive and Nutrition Contents of Bee Bread and Mathematical Modeling of Drying Characteristics. Issue 1 (8th December 2022) - Kutlu, Naciye; Gercek, Yusuf Can; Bayram, Nesrin Ecem
Abstract: In this study, the aim was to determine the effect of different drying methods (with microwave and hot air) on the color, nutrient and bioactive contents of fresh bee bread. Drying characteristics were also investigated. Microwave and hot air drying were applied at different microwave powers and temperatures, respectively. Lower moisture ratios and highest effective diffusion coefficients were obtained with microwave drying in a shorter time. The Midilli model was found to be the most suitable thin‐layer drying model for both methods. Regardless of the drying conditions, moisture, ash, protein, carbohydrate, and lipid proportions were observed to vary in the ranges of 4.9–8.2 %, 1.61–2.67 %, 17.47–32.54 %, 39.92–60.84 %, and 7.10–8.89 %, respectively. The lowest color difference was obtained for the sample dried at 210 W. As a result, it was determined that microwave drying is more suitable for preserving the nutritional and bioactive content of bee bread during drying. Abstract :